Effekter av feedback på mer respektive mindre komplexa arbetsuppgifter : Två fallstudier av Luleå tekniska universitet och TeliaSonera - Bengtsson, Emelie; Svensson, Sandra (2013)
Feedback is a commonly used concept in today’s society, as well as a central part of management accounting in organizations. It is also a powerful tool to achieve learning. Feedback, which also goes under the name performance evaluation, deals with evaluation of previous performances in order to provide information about the performances. The purpose of giving feedback is to enable improvement of the performance of the recipient, this by changing the recipient’s behavior. In what way feedback is given, as well as by whom it is given, affects how feedback is perceived and what effects it has. There are, in other words, many circumstances that affect feedback and its effects. The purpose of this study was to create an understanding of how task complexity affects how feedback can be given in order to result in positive effects on the feedback-recipient’s performance, and also to examine if there were potential differences. To find out how feedback can be given in order to have the desired effects, depending on the task complexity, a qualitative method was applied through case studies of two organizations where feedback is commonly occurring. The more complex task was studied in one organization, while the less complex task was studied in the other organization. Semi-structured interviews were conducted in both organizations and the result of the study showed that there are differences in how feedback is given to achieve the desired effects, depending on the task complexity. The study also pointed at both differences and similarities in how feedback is given on a more respectively less complex task. Validerat; 20130628 (global_studentproject_submitter)